Dose-response relationship between serum retinol levels and survival in patients with colorectal cancer: results from the DACHS study - Maalmi, Haifa; Owen, Robert; Ulrich, Alexis; Schöttker, Ben; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Nutrients, 2018)
Current knowledge on the role of retinol in the prognosis of patients with colorectal cancer (CRC) is very limited. We investigated the association of serum retinol levels with survival outcomes in a large cohort of 2908 CRC patients from Germany. Retinol concentrations were determined in serum collected shortly after diagnosis by mass spectrometry. Associations between serum retinol levels and survival outcomes were assessed using multivariable Cox regression and dose-response analyses. The joint association of serum retinol and serum 25-hydroxyvitamin D₃ (25(OH)D₃) with survival outcomes was also examined. During a median follow-up of 4.8 years, 787 deaths occurred, 573 of which were due to CRC. Dose-response curves showed an inverse relationship between serum retinol levels and survival endpoints in the range of <2.4 µmol/L, but no associations at higher levels. Low (<1.2 µmol/L) versus high (≥2.4 µmol/L) serum retinol levels were associated with poorer overall survival (Hazard ratio (HR) = 1.46, 95% confidence interval (CI) = 1.19⁻1.78, P-trend = 0.0003) and CRC-specific survival (HR = 1.69, 95% CI = 1.33⁻2.15, P-trend < 0.0001). Joint presence of low serum retinol (<1.2 µmol/L) and low 25(OH)D₃ (<30 nmol/L) was associated with a particularly strong decrease in overall and CRC-specific survival. Low serum retinol levels were identified as a predictor of poor survival in CRC patients, in particular when co-occurring with low serum concentrations of 25(OH)D₃. The clinical implications of these findings require further investigation.